Possibilities for the redefinition of the business model of CREPIB - Oliva, Edison Jair Duque; Preciado, Mariana Palacios; Gualdrón, Claudia Jessenia Becerra (Universidad Pedagógica y Tecnológica de Colombia, 2013)
In the context of redefining the CREPIB business model, the present study was performed to diagnose the current behavior and needs in the management of innovation, technological development and knowledge management of manufacturing companies of Boyacá. We found that 81% of firms are in low levels. Using multiple correspondence analyses, companies were classified into four groups, Group A firms should be strengthened, Group B firms should be driven, Group C firms should be appropriated and Group D firms should be aware in the management of innovation, technological development and knowledge management.